Bridging the digital divide: tailoring learning platforms for the elderly based on learning styles and digital skills - Songkram, Noawanit; Aulpaijidkul, Narongpon; Upapong, Supattraporn; Osuwanan, Hathaiphat; Thamsuwan, Pattarporn; Shidiq, Galih Albarra; Songkram, Nutthakorn (My University, 2026)
This study examines the relationship between learning styles and digital skills among older adults in Thailand to offer insights for the development of customized online learning platforms. A study was conducted on 706 participants aged between 60 and 78 years to evaluate their digital skills in four areas and learning styles according to Kolb’s model. Confirmatory factor analysis was performed to validate the four-factor model of digital skills. MANOVA results demonstrated significant variations in digital skills among learning styles, with convergers displaying superior proficiency in most areas. A matrix was created to outline the recommended functions of a learning platform with the objective of aligning pedagogical approaches with individual learning preferences and specific digital competencies. The results emphasized the significance of tailored methods in educating older adults on digital literacy and offered a framework for creating digital learning environments that are more comprehensive and efficient. This study intended to address the digital divide and improve the quality of life of older adults in a world that is increasingly becoming digital. Lastly, it posed implications for educational policy and practice.
Keywords: design matrix; digital skills; elderly; Learning platforms; learning styles